2016
DOI: 10.1103/physrevlett.116.194301
|View full text |Cite
|
Sign up to set email alerts
|

Slippery but Tough: The Rapid Fracture of Lubricated Frictional Interfaces

Abstract: We study the onset of friction for rough contacting blocks whose interface is coated with a thin lubrication layer. High speed measurements of the real contact area and stress fields near the interface reveal that propagating shear cracks mediate lubricated frictional motion. While lubricants reduce interface resistances, surprisingly, they significantly increase energy dissipated, Γ, during rupture. Moreover, lubricant viscosity affects the onset of friction but has no effect on Γ. Fracture mechanics provide … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 37 publications
(53 reference statements)
8
35
1
Order By: Relevance
“…Since Homalite is a viscoelastic material, we use the dynamic Young’s modulus E d =5.3 GPa (ref. 46) to compute the dynamic stress change4748, together with a Poisson’s ratio of ν =0.35 (refs 32, 49). Since the displacement fields are computed using the loaded specimen configuration as reference, the strains and stresses computed from these fields are changes over the reference configuration.…”
Section: Methodsmentioning
confidence: 99%
“…Since Homalite is a viscoelastic material, we use the dynamic Young’s modulus E d =5.3 GPa (ref. 46) to compute the dynamic stress change4748, together with a Poisson’s ratio of ν =0.35 (refs 32, 49). Since the displacement fields are computed using the loaded specimen configuration as reference, the strains and stresses computed from these fields are changes over the reference configuration.…”
Section: Methodsmentioning
confidence: 99%
“…As in dry friction, the onset of sliding of lubricated interfaces in the boundary lubrication regime is mediated by the propagation of rupture fronts. The variations of the strain fields created by these rupture fronts are also well described by LEFM (Figure c; Bayart et al, ). From a macroscopic point of view, a lubricant layer reduces the interfacial resistance to shear; that is, measured friction coefficients are smaller for a lubricated interface than for a dry one.…”
Section: Dynamics Of Interfacial Rupturesmentioning
confidence: 61%
“…Surprisingly, the fracture energy of a lubricated interface is higher than the value of Γ for the same nonlubricated (dry) interface. We have found that value of Γ does not depend on the viscosity of the lubricant used but, instead, on its chemical composition (Bayart et al, ). For example, when using hydrocarbon oils, Γ is still proportional to applied normal loads, but its value is an order of magnitude higher than for the same dry interface (Figure d).…”
Section: Dynamics Of Interfacial Rupturesmentioning
confidence: 95%
“…6(a). The addition of a thin layer of lubricant significantly increases Γ [33] and increase τ p − τ r but to a smaller extent than the increase in Γ, as can be concluded from the relative increase in x c (Eq. 3).…”
Section: Systematic Comparison Between Measurements and Lefmmentioning
confidence: 81%